Peran Guru Dalam Mengembangkan Kecerdasan Emosional Anak Di Pendidikan Dasar - Movitaria, Mega Adyna; Rahmadinur, Wisda; Delvia, Melda (Affection: Journal of Psychology And Counseling, 2024)
Many teachers do not have sufficient knowledge about emotional intelligence and how to develop it in children. In addition, the existing curriculum tends to emphasise cognitive and academic achievement, while emotional and social aspects are often neglected. Despite awareness of the importance of emotional intelligence, many teachers may not know how to implement effective strategies in their daily teaching. The purpose of this study is to identify and explore the role of teachers in developing children's emotional intelligence in primary education. The research method used was qualitative research with a case study research design to get a comprehensive picture of the role of teachers in developing children's emotional intelligence. The results found that teachers in primary education have an important role in developing children's emotional intelligence, but various challenges often hinder this role. Teachers' understanding of emotional intelligence varies widely, and this affects how they implement teaching strategies related to emotional development.